Analysis of tourists’ expenditures at the 2014 Sochi Olympic Games - Vetitnev, Alexandr; Bobina, Nadezhda; Zelenskaya, Olga (International Review of Management and Marketing, 2016)
The aim of the this study was to determine the Russian tourists’ expenditures during the 2014 Sochi Olympic Games, comparing these with tourists’ expenditures two year before and examine their affecting factors. The analysis showed that Olympic tourists’ expenditures were significantly higher than spending of other leisure travellers and amounted approximately US 2,000 per a trip. It was also found that the expenditures’ structure of Olympic tourists differed from other tourists due to the additional spending on the Olympic events and a higher cost of accommodation. The level of Olympic tourists’ expenditures was influenced by many socio-demographic and travel-related factors such as family income, occupation, type of accommodation, purpose of the trip.